2018
DOI: 10.1073/pnas.1800028115
|View full text |Cite
|
Sign up to set email alerts
|

Trends in health inequalities in 27 European countries

Abstract: Unfavorable health trends among the lowly educated have recently been reported from the United States. We analyzed health trends by education in European countries, paying particular attention to the possibility of recent trend interruptions, including interruptions related to the impact of the 2008 financial crisis. We collected and harmonized data on mortality from 1980 to 2014 for 17 countries covering 9.8 million deaths and data on self-reported morbidity from 2002 to 2014 for 27 countries covering 350,000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
137
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(157 citation statements)
references
References 38 publications
9
137
0
4
Order By: Relevance
“…The results of our study showed that absolute inequalities in cardiovascular mortality have often narrowed but relative inequalities mostly widened, confirming previous evidence 6 16. Researchers and policymakers do not agree on what measures to use for monitoring progress in tackling health inequalities, particularly on whether to use relative or absolute measures.…”
Section: Discussionsupporting
confidence: 63%
“…The results of our study showed that absolute inequalities in cardiovascular mortality have often narrowed but relative inequalities mostly widened, confirming previous evidence 6 16. Researchers and policymakers do not agree on what measures to use for monitoring progress in tackling health inequalities, particularly on whether to use relative or absolute measures.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, Leão et al dichotomised SRH but used only ‘bad’ and ‘very bad’ as poor SRH, in contrast to our measure of less than good SRH including the middle category of ‘moderate’ SRH. The same applies to the contrasting results reported by Mackenbach et al ,23 who found a continuing trend of declining prevalence of poor SRH across all educational groups with increasing relative inequalities in a pooled analysis of 27 European countries.…”
Section: Discussionsupporting
confidence: 57%
“…Leão et al 22 reported stable absolute and slightly increasing relative educational inequalities in SRH in a pooled analysis of data from 26 European countries, whereas absolute inequalities increased throughout the study period in some European countries, including Germany. Another recent study by Mackenbach et al 23 found a continuing trend of decreasing less-than-good SRH in a pooled analysis of Western European countries, with a faster decline among the highly educated and hence, increasing relative health inequalities.…”
Section: Introductionmentioning
confidence: 93%
“…As period of study, the 1980 -2014 years' interval has been taken in consideration. The type of the analysis was quasi-experimental on time series (Mackenbach et al, 2018). Other studies are investigating the impact of socioeconomic factors on HLY (Healthy Life Years) in the case of females and males, at the level of EU countries.…”
Section: Literature Reviewmentioning
confidence: 99%